1997
DOI: 10.1111/j.1432-1033.1997.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

7α‐Hydroxylation and 3‐Dehydrogenation Abolish the Ability of 25‐Hydroxycholesterol and 27‐Hydroxycholesterol to Induce Apoptosis in Thymocytes

Abstract: Oxygenated derivatives of sterols (oxysterols), including 25-hydroxycholesterol and 27-hydroxycholesterol, have immunosuppressive effects. Oxysterols can directly induce apoptosis in immature thymocytes, cells which are inherently sensitive to induction of programmed cell death. For that reason, the metabolism of 25-hydroxycholesterol and 27-hydroxycholesterol in mouse thymus has been studied. When incubated with thymic tissue, both oxysterols were found to be 7a-hydroxylated with subsequent oxidation to 7a-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…As to structure-function relations, Zhang et al have reported that 7α-hydroxylation and 3-dehydrogenation abolish the ability of 25OHC and 27-hydroxycholesterol to induce apoptosis in thymocytes (37). For the present study we find that the sterols tested can cause apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…As to structure-function relations, Zhang et al have reported that 7α-hydroxylation and 3-dehydrogenation abolish the ability of 25OHC and 27-hydroxycholesterol to induce apoptosis in thymocytes (37). For the present study we find that the sterols tested can cause apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…(17) There is some evidence for some OSstimulated DNA fragmentation in many cells i.e. endothelial cells, monocytes and macrophages, (58,59) smooth muscle cells, (60) lymphocytes (2,61) and thymocytes (62) (Table 4). Lizard et al (63) reported on the effects of various OS in causing apoptosis in bovine aortic endothelial cells.…”
Section: Oxycholesterols and Apoptosismentioning
confidence: 97%
“…The first step in the metabolism of 27-hydroxycholesterol in the brain is likely to be catalyzed by the oxysterol 7 ␣ -hydroxylase (CYP7B1), which is present at surprisingly high levels in the brain (25). Because 7 ␣ -hydroxylated metabolites of oxysterols may be less cytotoxic and also less inhibitory in relation to cholesterol synthesis (26)(27)(28), the high levels of CYP7B1 in the brain may be regarded as a protective mechanism. These metabolites must, however, be removed from the brain.…”
Section: Discussionmentioning
confidence: 99%